(untitled) (International Journal of Built Environment and Sustainability, 2025)
This study focuses on improving the interoperability of Building Information Modelling (BIM) and Building Energy Modelling (BEM) in Malaysia’s built environment, driven by the increasing adoption of BIM under high energy consumption conditions. Recognising the challenges related to data flow in BIM-BEM interoperability, the study aimed to identify critical energy-related properties for accurate energy performance analysis, assess interoperability issues between BIM and BEM models, and propose effective strategies. Through a mixed-methods approach combining quantitative data from questionnaire surveys with qualitative insights from semi-structured interviews, the findings highlighted the importance of energy-related properties in energy performance analysis, as well as interoperability issues such as data loss, limited data feedback loops and inaccuracies in data transition that affect the analysis results. Practical strategies recommended include middleware corrective tools, visual programming, and semantic enrichment to enhance data exchange and accuracy in energy analysis. The study was confirmed by high Cronbach’s alpha values ranging from 0.822 to 0.874 in reliability analysis, which ensures the credibility of the results. Ultimately, this study contributes theoretical advancements and practical guidance for industry stakeholders to promote sustainable construction practices, support the National Energy Efficiency Plan, align with the path toward Industrial Revolution 4.0, adopt global technologies, and enhance energy-saving and sustainable practices.